NCMP-01. THE ROLE OF VASCULAR ENDOTHELIAL GROWTH FACTOR RECEPTOR INHIBITORS IN PREVENTING CEREBRAL RADIATION NECROSIS: A RETROSPECTIVE COHORT STUDY. (9th November 2020) - Alnahhas, Iyad; Rayi, Appaji; Palmer, Joshua; Raval, Raju; Folefac, Edmund; Ong, Shirley; Giglio, Pierre; Puduvalli, Vinay
Abstract: INTRODUCTION: Radiation necrosis (RN) is a potential complication after radiation therapy to primary brain tumors and brain metastases. The pathophysiology of RN is not well understood but it is hypothesized that vascular endothelial growth factor (VEGF) plays an important role. Bevacizumab, a monoclonal antibody against VEGF-A, is often successful in the management of RN. The objective of this study is to assess whether VEGF receptor (VEGFR) inhibitors, a group of oral tyrosine kinase inhibitors (TKIs), can prevent or reverse cerebral radiation necrosis METHODS: We retrospectively studied a cohort of 102 patients with renal cell carcinoma (RCC) and brain metastases seen at The Ohio State University James Cancer Center between 01/01/2011 and 04/30/2019. We identified those who developed RN and analyzed the temporal relationship between the use of VEGFR TKIs and the development of RN. RESULTS: The cumulative incidence of RN in our cohort is 13.7% after radiation treatments that included LINAC-based stereotactic radiosurgery, fractionated stereotactic radiotherapy, or Gamma Knife radiosurgery. There was no statistically significant difference in the cumulative incidence of RN between patients taking TKIs and patients who were off TKIs (9.9% and 11.5% respectively, p= 0.741). The median time to development of RN was only numerically shorter in patients taking TKIs (151 versus 315 days, p=0.315). One patient developed RN after stopping cabozantinib. Three other patients developed RN while on cabozantinib. Two patients developed RN while on pazopanib, and 3 patients developed RN while on sunitinib. One patient was started on axitinib during active RN without significant improvement subsequently. CONCLUSIONS: VEGFR TKIs do not consistently prevent or reverse cerebral radiation necrosis and do not seem to have the efficacy that bevacizumab has against RN.